(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article analyzes the state’s attention to women during the period of renewal in Uzbekistan and the issues of increasing the social activity of women in the ongoing reforms. Also, the theoretical and legal foundations of increasing women’s rights and social activity have been studied.